2013
DOI: 10.1177/1060028013503127
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fluoxetine in Anorexia Nervosa Before and After Weight Restoration

Abstract: The risk-benefit ratio of fluoxetine in underweight and weight-restored patients with AN is undefined by clinical trials; therefore, clinical experience must be applied for its use in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Another line of evolving research suggests that olanzapine, an atypical antipsychotic, may also have merit as an adjunctive medication for patients with AN, with reported improvements in weight gain, anxiety and body image, although few adolescent-specific studies have been conducted to date [ 9 13 ]. To a similar degree, some conflicting research has shown that the use of fluoxetine, a selective serotonin reuptake inhibitor (SSRI), may reduce co-morbid symptoms of depression, anxiety, and obsessive compulsive disorder for weight-restored adult AN patients [ 14 16 ]. SSRIs are indicated for the treatment of anxiety and depression in adolescents without eating disorders [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another line of evolving research suggests that olanzapine, an atypical antipsychotic, may also have merit as an adjunctive medication for patients with AN, with reported improvements in weight gain, anxiety and body image, although few adolescent-specific studies have been conducted to date [ 9 13 ]. To a similar degree, some conflicting research has shown that the use of fluoxetine, a selective serotonin reuptake inhibitor (SSRI), may reduce co-morbid symptoms of depression, anxiety, and obsessive compulsive disorder for weight-restored adult AN patients [ 14 16 ]. SSRIs are indicated for the treatment of anxiety and depression in adolescents without eating disorders [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, to date no clinical trials have defined the riskbenefit ratio of fluoxetine pharmacotherapy in patients with AN, so practice relies still on clinical judgment (Sebaaly et al 2013). Treatment response may be moderated by weight restoration status, which was a factor in V.'s fluoxetine initiation in week 13 of her 16 week inpatient hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 45 reviews or meta-analyses, 26 were excluded for the following reasons: 16 were overviews and/or not systematic reviews with no explicit methodology for the selection of the papers mentioned [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24], one review [25] predated the World Federation of Societies of Biological Psychiatry review, one [26] reviewed the same eight studies as a meta-analysis included [27], five focused on unpublished data, or studies that were reviewed in later papers included here [28,29,30,31,32], one mainly focused on emerging treatment research or perspectives [33], two concerned oxytocin but with no specific results in AN [34,35].…”
Section: Methodsmentioning
confidence: 99%